(untitled) (Medical Forum Monthly, 2024)
Objective: To identify the correlation between hypothyroidism and serum anti-Mullerian hormone in infertile women. Study Design: Pre-experimental study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Pediatric and Maternity Teaching Hospital, Iraq Adiwaniyah Province from 2nd January 2023 to 15th January 2024. Methods: Eighty women diagnosed with infertility were enrolled. Results: The AMH levels were significantly lower in the adults with euthyroid. The AMH levels tended to be lower in subclinical hypothyroidism, although the differences were not significant. The AMH levels and hypothyroidism were significantly correlation while there is appositive relationship between level of AMH and age of women less than 30 years. Conclusion: A causal relationship between the infertile women's AMH levels and genetically determined thyroid function.